Non-registration of Muslim marriages in Malaysia: socio-legal implication - Md Hashim, Noraini (2009)
There are no single provisions found in the Al Qur´an or as Sunnah as relates to registration of marriage, but there are equally no prohibitory provisions as well. The purpose of the enforcement of registration is to remove the difficulty of proving the marriage. As such, the obligation to register marriage is important as it is for the benefit (maslahah) and protection of the society at large. The effect of unregistered marriage is not felt until and unless when the parties face matrimonial difficulties. The SharÊÑah court has no jurisdiction to entertain their cases until it is proven that their marriage is registered or deemed registered or valid according hukum shara´. Therefore, if the parties cannot prove the validity of their marriage by the assistance of the person solemnizing the marriage or by the witnesses of their marriage, the registration of the marriage will facilitate to prove the existence of their marriage. This article is to establish the importance of registration and the effect of non-registration that will lead to various socio-legal implications.